Kruppel expression during postembryonic development of Drosophila. - Hoshizaki, D.K. (Developmental Biology, 1994)
The Drosophila gap gene Krüppel (Kr) codes for a Zn2+ finger transcription factor important in embryo patterning, segment identity, and specification of various cell types. Based on Northern blot analysis, Kr function has been thought to be restricted to embryogenesis. I report here that Kr is also expressed during larval development, primarily in the fat body. Using both a P-element enhancer-trap line and a portion of the Kr promoter fused to lacZ, I find the activation of Kr in the fat body does not begin until the early-third-instar stage. Earlier in larval development, Kr is detected in the nerve cells associated with the gut. Kr's role as a transcription factor during early embryogenesis is well established. After gastrulation Kr protein is detected in a variety of cell types and is probably involved in cell specification. Kr is not detected in fat cells during embryogenesis nor during the first- and second-instar stages. The delayed expression of Kr in the fat cells occurs at a time in which the larva is undergoing a reprogramming in preparation for metamorphosis. It is possible that Kr serves as a transcriptional regulator in the fat body in this last larval instar. During this last larval stage, several fat-body-specific genes are transcriptionally activated in response to increasing levels of ecdysone. The possible role of Kr in the expression of these ecdysone-regulated genes is discussed.